Prediction of adult height using maturity-based cumulative height velocity curves - Sherar, L. B.; Mirwald, R. L.; Baxter-Jones, A. D. G.; Thomis, M. (The Journal of Pediatrics, 2005)
Objective: To validate and demonstrate how adult height can be predicted by using reference values obtained from maturity and sex-specific cumulative height velocity curves.